2018
DOI: 10.1136/bmjopen-2017-021160
|View full text |Cite
|
Sign up to set email alerts
|

Association between presenteeism and health-related quality of life among Japanese adults with chronic lower back pain: a retrospective observational study

Abstract: ObjectivesThis study investigated the relationship between presenteeism and health-related quality of life (HRQoL) among Japanese adults with chronic lower back pain (CLBP).DesignThis was a retrospective, cross-sectional study.SettingData were collected via a self-administered online survey of the Japanese adult general population.ParticipantsThe present study used 2014 Japan National Health and Wellness Survey (NHWS) data (n=30 000). Specifically, data were included from NHWS respondents who self-reported bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 36 publications
2
19
0
1
Order By: Relevance
“…Presenteeism is defined as health-related work productivity loss and being present at work while feeling unhealthy [ 14 , 15 ], which worsens the worker’s quality of life [ 16 , 17 ]. In this study, we defined presenteeism as work productivity loss.…”
Section: Introductionmentioning
confidence: 99%
“…Presenteeism is defined as health-related work productivity loss and being present at work while feeling unhealthy [ 14 , 15 ], which worsens the worker’s quality of life [ 16 , 17 ]. In this study, we defined presenteeism as work productivity loss.…”
Section: Introductionmentioning
confidence: 99%
“…This is related to low productivity and inability to perform their activities, which determines a loss in their general well-being and ends up compromising the dynamics of moving around to carry out their daily activities, culminating in changes in mood, leisure, sleep and quality of life, in addition to interfering negatively in interpersonal relationships. 31 Often, individuals report a negative self-perception when interacting socially, with frustration and shame when needing to perform their daily activities. There are even reports of little understanding of their illness not only from work colleagues, but from family members, partners and children.…”
Section: Discussionmentioning
confidence: 99%
“…Such pain is associated with daily activity impairment as well as loss of work productivity, which significantly impacts quality of life (QOL) ( 1 , 5 ). In a survey of Japanese adults and the UK Biobank study, greater pain severity and higher number of pain sites were associated with higher presenteeism ( 6 , 7 ). Another study demonstrated that the total incremental cost of health care due to pain was $635 billion in the United States ( 8 ).…”
Section: Introductionmentioning
confidence: 99%